2019
DOI: 10.1084/jem.20181290
|View full text |Cite
|
Sign up to set email alerts
|

Impaired αVβ8 and TGFβ signaling lead to microglial dysmaturation and neuromotor dysfunction

Abstract: Microglia play a pivotal role in the coordination of brain development and have emerged as a critical determinant in the progression of neurodegenerative diseases; however, the role of microglia in the onset and progression of neurodevelopmental disorders is less clear. Here we show that conditional deletion of αVβ8 from the central nervous system (Itgb8ΔCNS mice) blocks microglia in their normal stepwise development from immature precursors to mature microglia. These “dysmature” microglia appear to result fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 63 publications
7
52
2
Order By: Relevance
“…Several mouse mutants have been described as presenting brain vascular malformations during embryonic development. These mutants disrupt distinct signaling pathways, including TGF-β/integrin β8 (7,37), neuropilin-1 (38), and WNT/β-catenin (8,28). Some of these pathways may interact through unknown mechanisms to drive brain angiogenesis, since their individual mRNA levels comparable to control in our RNA-Seq from isolated brain endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…Several mouse mutants have been described as presenting brain vascular malformations during embryonic development. These mutants disrupt distinct signaling pathways, including TGF-β/integrin β8 (7,37), neuropilin-1 (38), and WNT/β-catenin (8,28). Some of these pathways may interact through unknown mechanisms to drive brain angiogenesis, since their individual mRNA levels comparable to control in our RNA-Seq from isolated brain endothelial cells.…”
Section: Discussionmentioning
confidence: 90%
“…Recent data suggest that defective TGFβ-regulated fatty acid metabolism in brain vascular endothelial cells contribute to the adult-onset neurological deficits (Tiwary et al, 2018). In addition, the progressive neurological deficits in mice lacking β8 integrin in the CNS have been linked to defective TGFβ receptor signaling in microglial cells (Arnold et al, 2019). Hence, the progressive neurodegeneration phenotypes in adult Itgb8-mutant mice may be due to defective TGFβ signaling in multiple cell types of the brain.…”
Section: Integrin αVβ8 Activation Of Latent Tgfβ Ecm Protein Ligandsmentioning
confidence: 99%
“…Further studies have clearly demonstrated that TGFβ1 is essential for microglia development [ 24 ] and maturation [ 25 ]. The deletion of TGFβ1 expression in the CNS [ 17 ], impairment of extracellular TGFβ1 processing and activation [ 26 , 27 ], or silencing of microglial TGFβ1 signaling by deletion of the TGFβ1 receptor Tgfbr2 [ 28 ] resulted in a loss of microglia maturation, characterized by a lack of homeostatic microglia marker expression. Moreover, affected microglia further display an inflammatory phenotype, as evidenced by the increased expression of ApoE , Axl , Cybb , Cd74 , H2-Aa , or Il1b , further emphasizing the importance of microglial TGFβ signaling to regulate microglia reactivity [ 28 , 29 ].…”
Section: Mouse Microglia Development and Maturation In Vivomentioning
confidence: 99%